Dalihan Na Tolu: Falsafah Perantau Batak Toba dalam Membangun Solidaritas di Kota Banjarmasin - Sitanggang, Ribka; Hakim, Arif Rahman (Huma: Jurnal Sosiologi, 2025)
This research is motivated by the existence of the philosophy of dalihan na tolu which is needed by Toba Batak nomads as a guideline to build solidarity and strong relationships between individuals or groups. The purpose of this study is to illustrate how Toba Batak nomads build solidarity based on the philosophy of dalihan na tolu in Banjarmasin City. The method used in this study uses a qualitative approach with a type of case study research. Participatory observation data collection techniques, semi-structured in-depth interviews and documentation. The research analysis used Emile Durkheim's theory of social solidarity. The results of the study provide an illustration of how Toba Batak nomads build solidarity based on the pretext of na tolu. This research shows that Toba Batak nomads in Banjarmasin City are very maintaining the philosophy of dalihan na tolu. Based on this philosophy there are three related things, namely the first, somba marhula-hula or respect for bones or uncles. Second, manat mardongan tubu or maintaining an attitude towards family friends. Third, elek marboru or meek towards women. The form of solidarity of Toba Batak nomads in Banjarmasin City is divided into several activities such as: 1) punguan (community), namely punguan marga parna (parna clan community) and Banjarmasin Batak Student Association (IMBB); 2) pangolion feast (wedding); 3) namonding (death) event; 4) a place of worship or church; 5) Other social activities such as lapo or café. Based on these activities, the key to building solidarity is tarombo (clan tree). So it can be concluded that the solidarity of fellow Toba Batak nomads in Banjarmasin City is still very thick and refers to the philosophy of dalihan na tolu as the foundation that regulates the activities of the Toba Batak nomad community.